Efficacy of high-versus moderate-dose statin therapy on lower extremity artery disease after revascularization - KEPEZ, ALPER (My University, 2022)
Aim: Statins are one of the most important agents in the treatment of atherosclerotic peripheral arterial disease. We aim to compare high – and moderate-dose statin therapy in patients with lower extremity artery disease (LEAD) who have undergone percutaneous transluminal angioplasty (PTA). Patients and Methods: Ninety-four patients treated with PTA were selected consecutively and retrospectively and were divided into two groups according to the high – or moderate-dose statin treatments they were given. Groups were compared for the absence of restenosis and occlusion as primary patency and the need for reintervention in the treated arterial segment as secondary patency. All patients underwent computed tomography (CT) angiography or duplex scan one year after receiving PTA. Results: Coronary revascularization (p<0.001) and prior statin usage (p:0.02) were more common in the high-dose statin group when compared to the moderate-dose statin group. Lesion characteristics did not differ between the two groups. Primary patency rate was significantly higher (36.1% vs. 27.6%, p 0.01) in the high-dose statin group. Major amputation (4.2% vs. 10.6%, p:0.03) and minor amputation (12.7% vs. 19.1%, p:0.03) rates were significantly lower in the high-dose statin group. Regression analysis revealed that the usage of high-dose statin therapy was an independent predictor of higher primary patency in patients who were treated with prior PTA(Odds ratio:2.208, p<0.001) Conclusion: High-dose long-term statin treatment might have better outcomes on primary patency in patients who underwent prior PTA for infrapopliteal lesions as a subgroup of peripheral artery disease. The administration of the high-dose long-term statin therapy might be important in the prognosis of peripheral arterial disease, especially for those with infrapopliteal lesions
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Family Practice; Fundamentals and Skills; General Health Professions; Pathophysiology; Internal Medicine; Assessment and Diagnosis; Medicine (miscellaneous); General Medicine; Statin treatment; Percutaneous transluminal angioplasty; Peripheral artery disease; RISK-FACTORS; ATORVASTATIN; OUTCOMES; METAANALYSIS; SIMVASTATIN; ANGIOPLASTY; Statin treatment; Percutaneous transluminal angioplasty; Peripheral artery disease